(untitled) (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
Economic theories of allocation will fäil to be effective unless they are able to categorically include the ecological integration of economic activities. However, »environmental assets« are significant - both as free (common land) property and as annuity bringing in retums. This article is first of all an attempt at illustrating this within the frame of societes constituted as nation-states. lt then goes on to widen its focus to include the global dimensions within which the allocation of the rights of use to environmental assets ( e.g. the atmosphere’s maximum limit of carbon dioxide pollution) has tobe viewed today. Dividing the world into groups of countries, however, shows how difficult it might be to come to an »allocative comprise« in this regard.